2004
DOI: 10.1159/000077797
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo-Oxygenase 2 Expression in Laryngeal Squamous Cell Carcinoma and Its Clinical Correlates

Abstract: Objective: To assess the significance of cyclo-oxygenase 2 (COX-2) in laryngeal squamous cell carcinoma (LSCC). Study Design: An immunohistochemical study in which 39 patients with LSCC were included. Methods: Immunohistochemical staining of the paraffin-embedded tumour tissues was performed using isoform-specific COX-2 polyclonal antisera (Santa Cruz, Calif., USA). COX-2 results were compared with the clinical parameters of the patients. Results: COX-2 was detected in all tumour tissues. In the normal larynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This study was conducted among 61 patients with stage I to IV larynx cancer having received different treatment modalities. Bayazit et al (31) found no correlation between COX-2 expression and survival, but this study was restricted to a small group of 39 patients with stage I to IV larynx cancer treated by surgery. All these studies were carried out on patients with different tumornode-metastasis stages and/or exposed to a variety of therapies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This study was conducted among 61 patients with stage I to IV larynx cancer having received different treatment modalities. Bayazit et al (31) found no correlation between COX-2 expression and survival, but this study was restricted to a small group of 39 patients with stage I to IV larynx cancer treated by surgery. All these studies were carried out on patients with different tumornode-metastasis stages and/or exposed to a variety of therapies.…”
Section: Discussionmentioning
confidence: 84%
“…High levels of COX-2 expression have been found in many cancers (15 -21) and have been associated with poor survival and increased risk of recurrence (22)(23)(24)(25)(26)(27)(28). In head and neck cancers, COX-2 overexpression has been clearly shown (29,30) but its effect on prognosis is still uncertain (12,(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…After the article titles and abstracts were checked, 38 articles were reviewed in detail [2259]. 9 studies were excluded as they did not provide sufficient data for extracting odds ratio (OR) or hazard ratio (HR) or 95% confidence intervals (CI) [2836], leaving 29 studies that fulfilled the eligibility criteria [2227, 3759] (Table 1). Four studies reported no site-specific HNC [24, 5457] and others recorded site-specific HNC.…”
Section: Resultsmentioning
confidence: 99%
“…COX-2 and its metabolites affect cell growth, and COX-2 can suppress the immune system and inhibit apoptosis, and is associated with the invasiveness of cancer. Overexpression of the COX-2 enzyme was reported in laryngeal carcinoma, and other head and neck tumors [28,29] . Overexpression of COX-2 should be more related to tumorigenesis and prognosis.…”
Section: Discussionmentioning
confidence: 99%